Analysis of Strategies to Improve People's Social Welfare in The Digital Era in Indonesia - Bayu Mogana Putra; Ridwan Adnan Erlangga (International Journal of Entrepreneurship and Sustainability Studies, 2022)
The equalization of the social welfare conditions of the people in Indonesia is still a problem for the government. This problem must be resolved immediately. The active participation of the community is one of the instruments that may help solve the problem of Indonesian people's social welfare, especially in the current digital world, where the conveniences we enjoy as a result of technological advancements are applied to aspects of social life. The purpose of the scientific work was to analyze and uncover ideal strategies to improve the social welfare conditions of people in Indonesia through the use of digital technology that has developed rapidly and productively in people's lives. The method used in this scientific work was an empirical legal research method because what was studied and examined was the process of working the Law in society. It was by studying social phenomena that involve social interaction in achieving common goals aligned with the mandate of applicable laws and regulations related to organizing social welfare in Indonesia. In the end, the analysis and study in this scientific work revealed the involvement of active participation of the community in improving the social welfare condition of the community through the use of digital technology. The progress and sophistication of digital technology systems nowadays have developed rapidly and are utilized productively in people's lives in Indonesia.